(untitled) (Journal of Laboratory Animal Science, 2018)
The study was conducted to evaluate the supplementation of Jojoba meal (Simmondisa Chinensis) on feed consumption, body weight changes, feed efficiency, and digestibility of nutrients in rabbits. A total of forty New Zealand white rabbits (4 week old) were randomly allotted to four dietary treatment groups of ten rabbits in each group. The control group (T0) was fed with complete feed with no Jojoba oil meal and test groups were fed complete feed with 5, 15 and 25% Jojoba oil meal in T1, T2 and T3 groups respectively. The daily dry matter intake in test groups were significantly (P≤ 0.05) reduced as compared to the control group. The average weekly body weight in test diet groups found significantly (P≤ 0.05) reduced consistently leading to reduction of body weight. Digestibility of either proximate principles (Dry matter, Organic matter, Crude fibre, Nitrogen free extractives) or fibre fractions (Neutral detergent fibre and Acid detergent fibre) was unaffected by jojoba supplementation whereas crude protein and ether extract digestibility and intake of total digestible nutrients and digestible crude protein were significantly lower in treated groups as compared to control group of rabbits.